AI in eye care; an introduction to how neural networks work. Issue 11 (November 2020) - Pead, Emma
Abstract : Dr Emma Pead looks at the development of an artificial intelligence system for the detection of age-related macular degeneration (C76731, one distance learning point suitable for optometrists and dispensing opticians)